Longitudinal analysis of academic stress and its effects on salivary cortisol, alpha-amylase, and academic outcomes: Study protocol. - Juan Luis Castillo-Navarrete; Alejandra Guzmán-Castillo; Claudio Bustos (PLoS ONE)
Introduction Academic stress is a prevalent problem among university students, affecting both their psychological well-being and academic performance. This study aims to investigate the mediating roles of biological and psycho-behavioural variables in the relationship between academic stress and academic performance over the course of a semester. Through a longitudinal approach and using accessible data collection technologies, the results will enable the design of effective interventions to mitigate the impact of academic stress. Hypotheses (i) Biological variables related to academic performance will mediate the relationship between academic stress and students' academic performance. (ii) Psycho-behavioural variables will also act as mediators in this relationship, impacting academic performance differently. General objective To explore the mediating roles of biological and psycho-behavioural variables in the relationship between academic stress and academic performance over the course of a university semester. Design A longitudinal non-experimental observational design will be applied. Data will be collected in three assessment cycles, each consisting of three consecutive weeks during the academic semester. Participants A sample of 160 undergraduate students from the Faculty of Medicine of the University of Concepción will be included. Students will be recruited on a voluntary basis through social networks and student associations. Students under psychological or pharmacological treatment will also be included to more representatively reflect the student reality and to ensure the ecological validity of the study. Biological and psycho-behavioural data collection Participants will answer electronic questionnaires on academic stress and psycho-behavioural variables three times a week via the REDCap platform. In addition, smart devices will be used to continuously collect biological data such as heart rate, oxygen saturation, and sleep patterns. Students will also collect saliva samples three times a week to measure cortisol levels, and alpha-amylase enzyme activity. Statistical analysis (i) Descriptive analysis of variables will be performed using measures of central tendency and dispersion for continuous variables and frequencies and percentages for categorical variables. (ii) Bivariate and multivariate analyses will be conducted to compare groups. (iii) Random intercept cross-lagged models will be used to assess the direction and reciprocal effects between variables over time. To analyze mediations, structural models (SEM) will be applied, considering biological and psycho-behavioural variables as mediators. Expected results It is anticipated that (i) biological variables, such as cortisol and salivary alpha-amylase, will play a significant mediating role in the relationship between academic stress and academic performance, particularly towards the end of the semester. (ii) psycho-behavioural variables will also have a mediating effect, with different impacts on academic performance depending on the level of stress experienced. The use of accessible technologies and non-invasive methods such as saliva sample collection will provide a replicable model for future research.